The economic consequence associated with integrated reporting: The effects on firms’ market Value - Zhao, Xinyu (2019)
This dissertation aims to examine the relationship between the adoption of IR and firms' market value and explore the difference between the effect of voluntary adoption and the overall effect of adopting IR. In order to do so, first, we focus on the firms complied by IR example database and examine whether the adoption of IR is value relevance. Next, we create a new variable which considers the pressures form countries and industries together, to reflect the degree of voluntary adoption and test the effect of the voluntary adoption of IR. Consistent with the prior literature about value relevance, our results show that the IR is positively associated with the firms' value, which indicates that the adoption of IR could enhance firms' market value. Also, according to our results, we find that the effect of the voluntary adoption of IR is better than the overall effect of the adoption of IR. Besides, the alternative approaches of panel data regression are used to verify our findings empirically, and robustness tests are implemented for each hypothesis.